In vitro maintenance of Angiostrongylus costaricensis does not provide physiological conditions for egg laying - Márcia Bohrer Mentz; Carlos Graeff-Teixeira (Sociedade Brasileira de Medicina Tropical (SBMT), 2005)
Fifteen pairs (male/female) of Angiostrongylus costaricensis were kept in vitro in Waymouth medium for three days to evaluate the amount and duration of egg laying. At 24, 48 and 72 hours, the mean egg counts were 321, 24 and 4 eggs/10 microliters, respectively. Most of the eggs were eliminated within the first 24 hours, suggesting they are expelled under non-physiological conditions. These results indicate that in vitro conditions are not appropriate for drug trials of egg-laying inhibitors for treatment of abdominal angiostrongylosis.